Determining fuzzy distance through non-self fuzzy contractions - Saha, Parbati; Guria, Shantanu; Choudhury, Binayak S. (Yugoslav Journal of Operations Research, 2019)
In the present work we solve the problem of finding the fuzzy distance between two subsets of a fuzzy metric space for which we use a non-self fuzzy contraction mapping from one set to the other. It is a fuzzy extension of the proximity point problem which is by its nature a problem of global optimization. The contraction is defined here by two control functions. We define a geometric property of the fuzzy metric space. The main result is illustrated with an example. Our result extends a fuzzy version of the Banach contraction mapping principle.